The role of national competitions in the athlete development pathway of athletes - Yamashita, S.; Goto, A.; Iwasaki, K.; Okai, R.; Awaki, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2025)
A study was conducted to examine the importance of making national competitions a milestone in the development of athletes, thus contributing to improvement of international competitiveness. The study focus was the National Sports Festival, which is included in the sport basic plan, as it helps to improve competitiveness by discovering and developing promising athletes. The research attempted to clarify to how national sports federations with excellent results in international competitions position national competitions in the athlete development pathway. Data were collected through semistructured interviews with staff involved in the management of national sports federation competitions and those responsible for athlete development. Steps for Coding and Theorization (SCAT) were used to analyze the collected data. Although interpretations of raw data can only be superficial, SCAT analysis allows the data to be decontextualized and recontextualized by constructing codes extracted from the context into a storyline, enabling in-depth meanings to be interpreted. The results suggested that for national competitions to function as a factor promoting athlete development, the following points should be considered: 1) they should identify promising athletes; 2) they should be linked to international competitions; and 3) they should overcome the differences in perspective between national sports federations and local stakeholders.